2017
DOI: 10.1021/acs.est.6b06531
|View full text |Cite
|
Sign up to set email alerts
|

Unique Rhizosphere Micro-characteristics Facilitate Phytoextraction of Multiple Metals in Soil by the Hyperaccumulating Plant Sedum alfredii

Abstract: Understanding the strategies that the roots of hyperaccumulating plants use to extract heavy metals from soils is important for optimizing phytoremediation. The rhizosphere characteristics of Sedum alfredii, a hyperaccumulator, were investigated 6 months after it had been planted in weathered field soils contaminated with 5.8 μg of Cd g, 1985.1 μg of Zn g, 667.5 μg of Pb g, and 698.8 μg of Cu g. In contrast with the non-hyperaccumulating ecotype (NHE), the hyperaccumulating ecotype (HE) of S. alfredii was more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…The actinobacterial genus Streptomyces was responsible for the majority of divergence among the rhizospheres of HE S. alfredii and bulk soils, contrasting with the rhizosphere of NHE S. alfredii. Our previous study also found HE harbored abundant Streptomyces in its rhizosphere during the phytoremediation of multimetalcontaminated soil (25). Streptomyces is the largest antibiotic-producing genus in the microbial world (49).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The actinobacterial genus Streptomyces was responsible for the majority of divergence among the rhizospheres of HE S. alfredii and bulk soils, contrasting with the rhizosphere of NHE S. alfredii. Our previous study also found HE harbored abundant Streptomyces in its rhizosphere during the phytoremediation of multimetalcontaminated soil (25). Streptomyces is the largest antibiotic-producing genus in the microbial world (49).…”
Section: Discussionmentioning
confidence: 84%
“…However, little knowledge is available regarding the basic ecology of indigenous soil microbial communities associated with the phytoextraction process in polluted soils by this plant species. Although our recent study indicated that the rhizosphere microcharacteristics, including the bacterial community, facilitate phytoextraction of multiple metals in soil by S. alfredii (25), the relationships between the bacterial rhizobiome and the influencing factors or variables, such as soil type, pollutant species, and pollution levels, are still unknown. Therefore, the present study investigated the characteristics of the rhizosphere bacterial community of the hyperaccumulator S. alfredii under different Cd treatments and the interaction of Cd presence and roots of S. alfredii on the structure of soil bacterial communities, using 16S rRNA gene amplicon sequencing.…”
mentioning
confidence: 99%
“…According to Figure 3 and Table 1, it can be speculated that the higher abundances of functional genes in the I of either soil are attributed to the special environment of the root surface that was more affected by the root radial oxygen loss and the physicochemical properties of the soils. Similarly, Hou et at predicted the functional genes of the bacterial communities in the rhizosphere of Sedum alfredii , a hyperaccumulator, and proposed that the compositional difference of predicted functional genes was a consequence of the special environment of the rhizosphere, which was severely polluted by heavy metals in their case [21]. Although PICRUSt is useful for supplementing 16S rRNA analyses in metagenome studies, it might lead to confusion when analyzing microbial communities that have a large proportion of poorly characterized populations [21].…”
Section: Resultsmentioning
confidence: 99%
“…Soil microbial richness and activity are closely related to the availability of soil nutrients. “Amino Acid Metabolism” were the energy and carbon sources of bacterial metabolism [ 44 ]. Thus, rhizosphere soil could promote more amino acid production and humic substance synthesis.…”
Section: Discussionmentioning
confidence: 99%